Evaluation Criteria of a Blended Massive Open Online Course Model in the Iraqi Universities - Ali, Qusay Abboodi; Shiratuddin, Norshuhada (2018)
A blended Massive Open Online Course (bMOOC) model in Higher Education Institutions (HEIs) in Iraq aims to improve the education of the Iraqi students and develop HEIs in the Iraq. It changes the trend of the traditional MOOC environments from only watching the video lectures passively by learners to a more flexible interaction in the learning process. In return, it solves the problem related to the lack of communication between classroom (face to face) and MOOC courses at the same time. This study describes the evaluation process of the Iraqi-bMOOC platform based on six criteria (blended learning, flexibility, high quality content, instructional design, network learning, and openness. Thus, this study has applied a survey to the Iraqi students to show their experiences in using the proposed model in two of the Iraqi universities (Tikrit & Bahgdad). Moreover, the results unveil that the learning activities are satisfying in the Iraqi-bMOOC courses.